(untitled) (International journal of artificial intelligence, 2026)
This article provides brief information about the lungs, an important organ of the human respiratory system. It also discusses the causes of pulmonary tuberculosis (TB), its main symptoms, progression outcomes, and possible complications. In addition, preventive measures against the disease are considered. The article aims to give a general understanding of pulmonary tuberculosis and to increase public awareness of preventive knowledge.